Lynne Tillman's Literary Ecologies: Affect, Cognition, and Signification in American Genius, A Comedy. Issue 3 (December 2019) - Rasmussen, Eric Dean
Abstract : Attuned to the need for ecologically informed criticism addressing the 'affective turn' in contemporary fiction, and following upon psychoanalytic critiques of the fantasies underlying neoliberal ideology, this article engages critically with questions concerning affect and meaning through a deliberate reading of Lynne Tillman's American Genius, A Comedy (2006). Tillman's encyclopaedic novel – narrated by an erudite, obsessive woman, Helen, afflicted with an irritating skin condition – is read as a cognitive-affective fiction that provides an oblique psychoanalysis of post-9/11 America: a neoliberal culture of would-be victims where the ascendant sensibility is hyper-sensitivity. While some literary theorists have recently advocated for phenomenological approaches less focused on interpretation and critique and more receptive to corporeal experiences, Helen's digressive, repetitive, skin-fixated narration reminds readers just how irritating, and funny, tangibility and 'presence effects' can be – precisely because of the curious way affects inevitably generate meaningful thinking. Tillman's artful syntax registers a heightened sensitivity to how affective forces in the environment, including language, stimulate our embodied minds and shape our thinking, feeling, and interactions. Much affect-studies scholarship claims affect circumvents semantics and resists being captured in language. But Tillman's writing, this article argues, contests notions of ineffable affect. Tillman's investment in transcribing affective phenomena, it is claimed, belies neither an individualistic or a solipsistic concern with subjective response, nor a radical materialist commitment to pushing the materialities of communication to the brink of meaninglessness. Affect, American Genius ingeniously demonstrates, is integral to eco-critical thinking. This account of affective circulations in American Genius demonstrates how Tillman successfully takes up the challenge of conveying, in prose, the complex, infra-linguistic affective processes underlying embodied communication and cognition. After introducing the novel, Section Two, 'Ambivalent Belief' explains how its opening prepares readers to confront what Slavoj Žižek calls the contemporary crisis of belief. Section Three tests and ultimately rejects the hypothesis that American Genius expresses a meaningless posthistoricist aesthetic; rather, Tillman's ecological aesthetic entails a meticulous staging of how imbricated cognitive processes are within the biological human body and political social body. Through her recursive prose, Tillman creates a mediating space for staging affectively inflected meta-cognitions. Section Four analyses passages where these meta-cognitions involve ecological perceptions. The critical focus throughout is on form. Deliberate readings reveal how, sentence by sentence, Tillman's 'skintax' evokes multidimensional corporeal processes that constitute the affective dimension of thinking. 'Sensitivity and Making Sense', the Fifth Section, identifies the ethical core of Tillman's eco-aesthetic and unpacks passages that expand the concept of sensitivity in ways that attune readers to affective modulations of the social that are potentially transformative.